Characteristics, Determinants, Challenges and Performance of Self-employment among the Youth in Uganda - Barugahara, Florence; Barungi, Mildred (International Journal of Economics and Financial Issues, 2023)
This study examined the characteristics, determinants, challenges and performance of self-employment among the youth in Uganda using the School-to-Work Transition survey data for 2015 collected by the Uganda Bureau of Statistics. We employed two analytical approaches: descriptive statistics and binary and multivariate probit models. We found that most employed youths are self–employed. The majority of the youth were poor and had acquired primary education or less. Econometric estimations indicate that self-employment is determined by age, the number of children, financial status, education, high-income motive and flexible work hours. Most youth started businesses with individual savings or family money but not bank loans. Most youth faced unique problems, but financial constraints followed by market competition were the main challenges faced by the self-employed youth. Self-employment is not lucrative, and 20.29% of self-employed youths do not make profits from their entrepreneurial efforts. Moreover, 78.83% of the self-employed youths live below the poverty line.